Hypericum sampsonii Hance: a review of its botany, traditional uses, phytochemistry, biological activity, and safety - Sun, Zhanghua; Li, Yanzhen; Zhong, Ruimin; Li, Ran (Frontiers in Pharmacology, 2023)
Ethnopharmacological relevance: Hypericum sampsonii Hance, also known as Yuanbao Cao in Chinese, is a traditional medicinal herb from the Guttiferae family and has been widely used in China to treat various conditions, including dysentery, enteritis, mastitis, scrofula, and contusion. Aim of the review: This review aims to provide a comprehensive overview of the botany, traditional uses, phytochemistry, biological activity and safety of H. sampsonii and to highlight its potential for medical application and drug development. Materials and methods: We searched several databases, i.e., Web of Science, SciFinder, PubMed, CBM, CNKI, Google Scholar, etc., for relevant information on H. sampsonii. Additionally, we also consulted some books on Chinese medicine. Results: To date, 227 secondary metabolites have been isolated from H. sampsonii, including polycyclic polyprenylated acylphloroglucinols (PPAPs), benzophenones, xanthones, flavonoids, naphthodianthrones, anthraquinones and aromatic compounds. These metabolites exhibit various biological activities such as anti-inflammatory, anti-tumor, anti-depressant, anti-oxidant, anti-viral and anti-bacterial effects. PPAPs are considered the main active metabolites with rich biological activities. Despite being known as rich source of PPAPs, the full extent of H. sampsonii biological activities, including their potential as PDE4 inhibitors, remained unclear. Since, previous studies have mainly been based on structural identification of metabolites in H. sampsonii, and efficacy evaluations of these metabolites based on clinical applications of H. sampsonii lack sufficient data. However, current evidence suggest that PPAPs are the most likely material basis for efficacy. From the limited information available so far, there is no evidence of potential safety issues and the safety data are limited. Conclusion: Collectively, this review provides a comprehensive overview of the botany, traditional uses, phytochemistry, pharmacology, and safety of H. sampsonii, a valuable medicinal plant in China with various pharmacological activities. Based on pharmacological studies, H. sampsonii shows potential for treating gastrointestinal and gynecological disorders as well as traumatic injuries, which aligns with traditional medicinal use due to the presence of PPAPs, benzophenones, xanthones, and flavonoids. Therefore, further studies are needed to evaluate the pharmacological effects and elucidate the pharmacological mechanisms. In addition, pharmacological mechanisms and safety evaluation of PPAPs on animal models need to be clarified. Yet, further comprehensive studies are required to elucidate the phytochemical constituents, pharmacological mechanisms, structure-activity relationships, safety evaluation, and quality standards of this plant. Takentogether, this review highlights the potential of H. sampsonii for medical application and drug development.